From manual to electronic road congestion pricing: The Singapore experience and experiment - PHANG, Sock-Yong (Institutional Knowledge at Singapore Management University, 1997)
This study reviews the efforts of Singapore to curb road congestion through restraints on motor vehicle ownership as well as user fees. In particular, it traces the history of the famous Area Licensing Scheme (ALS), and then discusses its shortcomings, also the need for Electronic Road Pricing (ERP), its advantages and disadvantages and the technology involved in this state of the art system. This paper identifies important research questions to be addressed in connection with the first full-scale adoption of ERP.